Kemudahan Mencari Referensi Dengan LMS UNIKOM - Amalina, Nurriska (Forum Perpustakaan Perguruan Tinggi Indonesia, 2022)
The Covid-19 pandemic has profoundly impacted the education and work sectors, resulting in significant transformations. The prevalence of online learning and remote employment has necessitated adaptation within numerous institutions, including university libraries like the Unikom Library, to cater to the needs of their readers effectively. Initially, the Unikom Library encountered challenges due to its primary emphasis on printed books in its collection, with digital collections not yet receiving significant attention. This poses a challenge in delivering sufficient services. To address this issue, the Unikom Library implemented an innovative approach by incorporating electronic materials into the Learning Management System (LMS), namely Moodle, a platform for online education. This aims to comprehensively account for successfully integrating the Unikom Library e-resources program with the LMS, employing a unified access approach. Consequently, incorporating library materials into the LMS has demonstrated significant efficacy amidst the epidemic, as evidenced by increased user engagement. This observation indicates that the electronic resources accessible through the LMS at the Unikom Library have emerged as a viable and efficient option for readers seeking reference materials. The integration of electronic resources with the LMS has been beneficial for the Unikom Library, enabling it to maintain its relevance and effectively cater to the needs of its users among the challenges posed by the current circumstances. The statement above underscores the significance of adaptability and innovation as crucial factors in addressing the various issues encountered by educational institutions and libraries amidst the digital era and ongoing pandemic.